THE EFFECT OF PACKAGING, PRICE, BRAND AWARENESS ON CUSTOMER LOYALTY OF PT. KREASI NOSTRA MANDIRI: (STUDIES CASE ON CUSTOMER APK VEGETABLE BOX, JABODETABEK) - Dasa Rahardjo Soesanto; Agatha, Aurelia (EZRA SCIENCE BULLETIN, 2025)
The Indonesian e-commerce industry is developing in a direction that looks increasingly promising. Brand loyalty is continued to influence family members to buy brands. This study aims to analyze the magnitude of the influence of packaging on loyalty in the vegetable box application. To analyze the magnitude of the influence of price on loyalty in the vegetable box application. To analyze the magnitude of the influence of brand awareness on loyalty in the vegetable box application. To analyze the magnitude of the influence of packaging, price and brand awareness together on loyalty in the vegetable box application. This study is included in the title of quantitative research. The population of this study is all users of the vegetable box application. The researchers in this study use non - probability techniques sampling, namely technique purposive sampling. The results of this study are that packaging has a positive effect on Loyalty. Price has a positive effect on Loyalty. Brand Awareness has a positive effect on Loyalty.